Peningkatan Hasil Belajar Keterampilan Menulis Teks Prosedur melalui Penerapan Pembelajaran Berdiferensiasi Peserta Didik Kelas VII.1 UPTD SMP Negeri 3 Kec. Harau Semester Ganjil Tahun Pelajaran 2024-2025 - Widyastuti, Indri; Afnita, Afnita (AHKAM, 2025)
The phenomenon of low procedural text writing skills among students indicates an urgent need for a learning approach that can accommodate the diverse learning needs of students. This study aims to improve the ability to write procedural texts through differentiated learning for seventh-grade students of UPTD SMPN 3 Kecamatan Harau. This research is a classroom action research (CAR) conducted in two cycles. The subjects of the study are 26 students from class VII.1. Data collection techniques were carried out through observation, interviews, performance tests on writing, and documentation. The research instruments included observation sheets for teacher and student activities, interview guidelines, and a rubric for assessing procedural text writing. Data were analyzed using both quantitative and qualitative descriptive analysis techniques. The results of the study indicate an improvement in students' procedural text writing skills, both in terms of structure, content, and language, after the implementation of differentiated learning. This is evident from the increase in the average scores of student learning outcomes from cycle I to cycle II, as well as the increased active involvement of students in the learning process. The conclusion of this study is that differentiated learning is effective in improving students' procedural text writing skills, as it can optimally accommodate students' interests, needs, and learning profiles.